ANALISIS YURIDIS PERJANJIAN PEMBIAYAAN KONSUMEN DAN AKIBAT HUKUM JIKA TERJADI WANPRESTASI DALAM PERJANJIAN PEMBIAYAAN KONSUMEN DI INDONESIA - Umul Khair (JCH (Jurnal Cendekia Hukum), 2017)
In Article 1329 of the Civil Code, the agreement is divided into 2 (two) kinds, namely the named agreement (nominaat) and unnamed agreement (innominaat). Contracts or agreements develope at this time as a logical consequence of the development of business cooperation between business actors. In a treaty there is one part bind itself to another part. Consumer financing is an agreement not specifically regulated in the Civil Code, but since the book III of the Civil Code embraces an open system, parties may enter into agreements not specifically regulated in the Civil Code. The consumer financing agreement as an Innominaat agreement is also subject to general terms of agreement. In this study using normative research methods, where the authors can examine and can also learn the norms contained in legislation or norms that regulated the principle of freedom of contract according to the Civil Code so that in its implementation in accordance with applicable regulations. The results show how the implementation of consumer financing agreements in Indonesia and how the legal consequences in case of default in consumer financing agreements. First, basically the consumer financing agreement in Indonesia is conducted like other agreements in general. Consumer Financing Agreement is not like a sale or purchase agreement or a lease, but the consumer financing agreement is a combination of both applicable by the parties exercising the rights and obligations in the agreement as described above. Second, the result of the law in case of default, the agreement does not need to be requested for cancellation, but by itself has been null and void, but the provisions of Article 1266 paragraph 2 explain that the consequences of the law of default are not null and void, but must be annulled to the judge. Subsequently Article 1244- Article 1252 of the Criminal Code describes the compensation for default, namely, by paying the actual losses suffered, the fees used, and allowed to cease the expected loss of profits.